ANALISIS UNGKAPAN CINTA DALAM FILM WHATâ€™S EATING GILBERT GRAPE PRODUKSI LASSE HALLSTROM - UDANG, MARHEIN; WANTASEN, ISNAWATY L.; RATTU, JULTJE A.J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ This research is entitled â€œUngkapan Cinta dalam Film Whatâ€™s Eating Gilbert Grape produksi Lasse Hallstromâ€. It is written to fulfill the requirement of accomplishing bachelorâ€™s degree in English Department Faculty of Humanities Sam Ratulangi University. The focus of this research is love expressions in the film. This research includes the kinds of love expression and the portrayed of love expressions. The writer used concepts from Collier (2014) and Grande (2016) as well as theory from Fromm (1998) to identify and classify the data. The writer also used the theory from Snyder (2011) to analyze the love expressions in the film â€œWhatâ€™s Eating Gilbert Grapeâ€. The result of this research shows 7 types of love expressed in 9 types of love expression. The 7 types of love are love as answer of human existence, love between parent and child, brotherly love motherly love, erotic love, love-Self, and love of god. The 9 types of love expression are spending time together, giving something or gift, receiving something or gift, motivating, giving appreciation, doing helpful behaviors, doing physical affection, believing in each other, and emotional overflowing.Keywords: Love, Emotional Expression, Expression of Love, Film, Theory of Film